Genome-Wide Differential DNA Methylation in Reproductive, Morphological, and Visual System Differences Between Queen Bee and Worker Bee (Apis mellifera) - Wang, Hongfang; Liu, Zhenguo; Wang, Ying; Ma, Lanting; Zhang, Weixing; Xu, Baohua (Frontiers in Genetics, 2020)
There are many differences in external morphology and internal physiology between the Apis mellifera queen bee and worker bee, some of which are relevant to beekeeping production. These include reproductive traits, body size, royal jelly-secreting properties, and visual development, among others. The identification of candidate genes that control the differentiation of these traits is critical for selective honeybee breeding programs. In this study, we compared the genomic methylation of queen bee and worker bee larvae at 3, 4, and 5 days of age by whole-genome bisulfite sequencing, and found that the basic characteristics of genomic methylation in queen and worker larvae were the same. There were approximately 49 million cytosines in the Apis larvae genome, of which about 90000 were methylated. Methylated CpG sites accounted for 99% of the methylated cytosines, and methylation mainly occurred in exons. However, methylation levels of queen and worker larvae showed different trends with age: the methylation level of queen larvae varied with age in an inverted parabola, while the corresponding trend for worker larvae with resembled an exponential curve with a platform. The methylation level of queen larvae was higher than that of worker larvae at 3 days of age, lower than that of worker larvae at 4 days of age, and similar to that of worker larvae at 5 days old. The top 10 differentially methylated genes (DMGs) and 13 caste-specific methylated genes were listed, and correlations with caste determination were speculated. We additionally screened DMGs between queen larvae and worker larvae involved in specific organ differentiation as well as reproduction, morphology, and vision differentiation during caste determination. These genes are potential molecular markers for selective breeding of A. mellifera to improve fecundity, royal jelly production, body size, and foraging, and represent candidate genes for investigating specialized functional segregation during the process of caste differentiation.